2004
DOI: 10.1007/bf02287340
|View full text |Cite
|
Sign up to set email alerts
|

Externally caused deaths for adults with substance use and mental disorders

Abstract: For decades, there have been reports of shorter life expectancy among those with mental illness, especially those with more serious psychiatric disorders. The purpose of this study was to compare the risk of mortality among Medicaid beneficiaries, aged 18-64 years, treated for mental illness to a comparable group who were not mentally ill and to the general population. The data used were from the Massachusetts Division of Medical Assistance and records of deaths from the Department of Public Health in Massachu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
(2 reference statements)
0
25
0
Order By: Relevance
“…More generally, mental disorders are linked to poor health through unhealthy lifestyle [25,26], physical consequences of psychotropic medication [3], and problems accessing medical care [27]; some or all of these factors may account for reduced survival in people with PD. Substance use disorders are a major cause of death and disability [1,9] and frequently co-occur with PD, particularly in young people with Cluster B PD [28], and the particularly high SMR for Cluster B PD may reflect unhealthy lifestyles characterised by heavy substance use and smoking. Patients with PD are often prescribed excessive doses of psychotropic and non-psychotropic medications [29] which themselves may potentially lead to unwanted physical consequences.…”
Section: Possible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, mental disorders are linked to poor health through unhealthy lifestyle [25,26], physical consequences of psychotropic medication [3], and problems accessing medical care [27]; some or all of these factors may account for reduced survival in people with PD. Substance use disorders are a major cause of death and disability [1,9] and frequently co-occur with PD, particularly in young people with Cluster B PD [28], and the particularly high SMR for Cluster B PD may reflect unhealthy lifestyles characterised by heavy substance use and smoking. Patients with PD are often prescribed excessive doses of psychotropic and non-psychotropic medications [29] which themselves may potentially lead to unwanted physical consequences.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…People with mental disorders die prematurely for a variety of reasons, including poor physical health [3][4][5], adverse physiological consequences of long term psychotropic medication, unhealthy lifestyle [5], as well as increased death rates as a result of suicide, accidents and homicide [6][7][8]. The risk of increased mortality has been shown to vary according to type of mental disorder, with substance use disorders conferring a particularly high risk of early death [1,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with undiagnosed or untreated mental illness have a higher risk of dying prematurely from unintentional and intentional violence. 1,2,3,4 Evert, et al 5 , recommend that public health planners have better access to mortality information to identify and prioritize policy, resources, and health promotion activities for special populations.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,7,8,9 Previously published studies in this area have been limited to mental illness population subgroups, e.g., severe mental illness patients using inpatient, residential or case management services, or Medicaid enrollees. 2,4,10 To address the sample limitations of previous studies, we linked all Ohio deaths (438,749) with deaths within the Ohio publicly-funded system (30,219 deaths identified, including 14,506 with mental health service claims, out of 1.3 million living individuals). We did not include in the analysis of this study deaths of individuals identified within the ODMH databases who did not receive services through ODMH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation